1999
DOI: 10.1046/j.1439-0507.1999.00266.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic mycoses during prophylactical use of liposomal amphotericin B (Ambisome®) after liver transplantation

Abstract: We investigated the prophylactical administration of liposomal amphotericin B (Ambisome) in the early phase after liver transplantation (LTx). Fifty-eight patients received Ambisome prophylactically after LTx. Ambisome (1 mg kg-1 day-1) was given intravenously for 7 days after LTx. Immunosuppressive prophylaxis was cyclosporin A (CsA) based in 11 patients. Forty-seven patients had a tacrolimus-based immunosuppressive regimen. CsA and tacrolimus dosages were adjusted to trough levels of 150-250 ng ml-1 (EMIT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 31 publications
1
31
0
2
Order By: Relevance
“…Low doses (1 mg/kg/day) of lipid formulations of amphotericin B have also not been effective in case series (171,321). Breakthrough infections were documented in 5% of the patients in one study (171) and in 10% in another (321) in which Ambisome at 1 mg/kg/day was used.…”
Section: Organ Transplant Recipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low doses (1 mg/kg/day) of lipid formulations of amphotericin B have also not been effective in case series (171,321). Breakthrough infections were documented in 5% of the patients in one study (171) and in 10% in another (321) in which Ambisome at 1 mg/kg/day was used.…”
Section: Organ Transplant Recipientsmentioning
confidence: 99%
“…Low doses (1 mg/kg/day) of lipid formulations of amphotericin B have also not been effective in case series (171,321). Breakthrough infections were documented in 5% of the patients in one study (171) and in 10% in another (321) in which Ambisome at 1 mg/kg/day was used. A lack of cases of invasive aspergillosis precluded meaningful assessment of the efficacy of 1 mg of liposomal amphotericin B (Ambisome)/kg/day as prophylaxis against Aspergillus infections in a randomized trial (315).…”
Section: Organ Transplant Recipientsmentioning
confidence: 99%
“…Low-dose amphotericin B not only was ineffective but, in fact, increased the risk of invasive aspergillosis after liver transplantation [30]. Likewise, low doses of lipid formulations of amphotericin B (1 mg/kg/day) have not been shown to be effective [31,32]. Concerns regarding poor bioavailability and absorption in the immediate posttransplantation period dissuade from the use of itraconazole as a potential candidate for prophylactic studies among transplant recipients.…”
Section: Design Issues Concerning Invasive Aspergillosis In Liver Tramentioning
confidence: 99%
“…Also, the majority of the available studies were published more than a decade ago. The study by Mora et al [10] used conventional amphotericin B in a dose of 1 mg/kg during 5 days; the study by Braun et al [11] used different doses of L-AmB, from 1 to 5 mg/kg until the discharge from the ICU); Lorf et al [12] used a dose of 5 mg/kg/day of LAmB for 7 days; Castroagudin et al [13] used a dose of 1 mg/ kg L-AmB for 7 to 10 days. Nonetheless, all these studies concluded that this prophylaxis is effective in high-risk groups.…”
Section: Discussionmentioning
confidence: 99%